Inoculation with plant growth-promoting bacteria mitigates the negative impacts of 2 °C warming on the photosynthesis, growth, and nutritional value of a tropical C4 grassland under field conditions - Habermann, Eduardo; Riul, Beatriz Neroni; Nóbile, Fábio Henrique Moscardini; Santana, Ramon Martins; Oliveira, Kamilla Silva [UNESP]; de Souza Marques, Bruno; Dias de Oliveira, Eduardo Augusto; Branco, Roberto Botelho Ferraz; Costa, Kátia Aparecida de Pinho; Hungria, Mariangela; Nogueira, Marco Antônio; Martinez, Carlos Alberto (Elsevier, 2025)
Human-induced climate change is causing Earth's temperature to rise, and models indicate a persistent increase in the next years. Temperature is one of the most important factors regulating the carbon flux of natural and managed ecosystems. In the last decades, the use of plant growth-promoting bacteria in C4 grasses has emerged as an important alternative to alleviate the negative impacts of abiotic factors on plant metabolism, growth, and forage nutritional quality. In this study, we investigated the effects of warming (+2 °C) on the photosynthesis, plant water status, growth, and nutritional quality of a managed pasture of Brachiaria (syn. Urochloa) Mavuno inoculated or not with Azospirillum brasilense and Pseudomonas fluorescens. We evaluated two levels of temperature (ambient and elevated) under two levels of inoculation (inoculated and non-inoculated) in a multifactorial design. Our results showed that inoculation stimulated root growth and increased photosynthetic rates through higher stomatal conductance and improved photosystem II performance, presumably resulting in higher productivity, crude protein content, and forage digestibility with reduced lignin and fiber fraction. Warming increased non-photochemical quenching and electron transport rate in the wet season, but decreased midday maximum quantum efficiency of PSII photochemistry during dry season, relative water content, productivity, and forage quality and digestibility. When inoculated plants developed under a warmer atmosphere, the positive effects of inoculation completely counteract the negative impacts of warming on photosynthesis, growth, nutritional quality, and digestibility, resulting in a pasture with reduced lignin content and improved heating dissipating capacity and digestibility. Our results demonstrated that A. brasilense and P. fluorescens co-inoculation is a sustainable option to fully mitigate the negative impacts of elevated temperature on Mavuno grass pastures. These findings highlight the potential of microbial inoculants in enhancing forage resilience and productivity under climate stress.
Keywords: Azospirillum brasilense; Inoculation; Pseudomonas fluorescens; Solutions for mitigation; T-FACE; Tropical climate; Tropical forage; Warming